[View of the constructing of Kennedy Library] - P. K. Phillips::::::photographer::: (1978)
View of the constructing of Kennedy Library, from the adjacent four way traffic stop. The crane is prominently pictured. The first floor is the only level constructed. Pedestrians and cars are stopped on the street, in front of the construction site.